Rolnictwo w Polsce Ludowej - Ratajczak, Klemens (Wydział Prawa i Administracji UAM, 1984)
The article is opened with a presentation of conditions of Polish agriculture at the end of the World War Two. The author also explains reasons of the agrarian reform and its effect on increase of production and economic revival in the country. The author indicates that the reform was not as much a politicai act as the economic one, which resulted in the most rational adjustement of organizational and property relations to the then présent productive forces both in agriculture and in the whole of economy. In he beginning of fifties that most efficient model of agriculture in the Polish conditions was disturbed. That led to stagnation and even to a decline in some branches of agricultural production. A period of removing all negative tendencies present in agrarian policies since 1950 became from 1958 on. The years of 1970 - -1974 were the most prosperous time for the Polish agriculture and its production reached the highest output gains in its all post-war history. Yet, several distortions were not avoided, like unjustified pace of concentration and bureaucratization in managing state farms, insufficient developement of production means of industrial origin for agriculture, departures from the 1970 adopted policy of one agriculture. After 1980 the agricultural policies were set to eliminate those irregularities. It is however carried out under conditions of substantial difficulties connected with the present economic crisis.
Agriculture in People's Poland